Pre-Antibiotic Treatment Followed by Prolonged Repeated Faecal Microbiota Transplantation Improves Symptoms and Quality of Life in Patients with Irritable Bowel Syndrome: An Observational Australian Clinical Experience - Harrison Hamblin; Anoja W. Gunaratne; Annabel Clancy; Denise Pilarinos; Antoinette LeBusque; Marie Vic M. Dawson; Thomas J. Borody (Gastroenterology Research and Practice)
Background. The use of faecal microbiota transplantation (FMT) in irritable bowel syndrome (IBS) has frequently failed to induce long-term symptomatic improvement. The use of multiple FMT infusions is one proposed mechanism through which the efficacy of FMT can be amplified. Aims. To evaluate the safety and efficacy of a novel six-month FMT treatment protocol in IBS. Methods. Patients diagnosed with IBS confirmed by Rome IV Criteria were recruited for single-centre, single-arm, prospective clinical observational study. Participants received one colonoscopically delivered FMT followed by 36 rectal enemas across a six-month period. Validated abdominal symptoms and Short-Form (SF-36) Quality of Life (QOL) questionnaires were collected at baseline, week-12, week-24, and week-56, respectively. Wilcoxon matched-pairs signed-rank tests were conducted to compare differences in abdominal symptom and SF-36 QOL scores over the follow-up timepoints. Statistical significance was set at 5%. Results. Sixty participants diagnosed with IBS [IBS-constipation (n=27), IBS-diarrhoea (n=18), and IBS-mixed (n=15)] received the six-month FMT treatment. IBS symptom severity reduction was achieved in up to 61% of respondents at week-12, 64% of respondents at week-24, and maintained in up to 75% of respondents at week-52. Long-term reduction in symptom severity was associated with an increase in QOL, achieved in up to 64% of respondents at week-52 when compared to baseline. Adverse events were experienced in 28% of participants, though they were both transient and mild in nature. Conclusions. Six-month sustained FMT appears to be both safe and effective in the short- and long-term alleviation of IBS associated symptoms as well as improving participant QOL.